2011
DOI: 10.1007/s10517-011-1141-2
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Gene Polymorphism in Men with Coronary Atherosclerosis in Siberia

Abstract: Polymorphism of coding fragment of APOE gene was analyzed in two groups of men. The main group consisted of 77 residents of the West Siberian region aged 45-65 years with coronary atherosclerosis (documented by coronary angiography) without acute coronary syndrome with stable effort angina, functional class II-IV. The reference group consisted of 350 residents of Novosibirsk, aged 45-69 years. Statistically significant associations between genotypes of APOE gene coding part polymorphism and some key lipid risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Atherosclerosis is an important pathophysiological basis of CI. APOE gene polymorphisms have been shown to be associated with atherosclerosis [29,30]. However, the results of previous studies on the relationship between APOE gene polymorphisms and CI are not very consistent.…”
Section: Discussionmentioning
confidence: 92%
“…Atherosclerosis is an important pathophysiological basis of CI. APOE gene polymorphisms have been shown to be associated with atherosclerosis [29,30]. However, the results of previous studies on the relationship between APOE gene polymorphisms and CI are not very consistent.…”
Section: Discussionmentioning
confidence: 92%
“…CAD is considered to result from an interaction between genetic and environmental factors [4]. Several studies have suggested that APOE variants increased the risk of developing CAD [21,22]. It is noted that this was the first to identify an association between APOE polymorphisms and the risk of CAD in postmenopausal Hakka women in southern China.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is an important pathophysiology basis of CI. APOE gene polymorphisms have been shown to be associated with atherosclerosis [20,21]. However, the results of previous studies on the relationship between APOE gene polymorphisms and CI were still not very consistent.…”
Section: Discussionmentioning
confidence: 92%